Alternativas energéticas para uma termoelétrica no nordeste brasileiro: evidências econômicas sob condições de risco - Fonseca, Amadeu Junior da Silva (2022)
Due to the global decarbonization goals, there are constant debates about the use of fossil fuels, renewable sources and the energy transition process. In the early 2000s, there were auctions for the contraction of fuel oil thermoelectric plants in Brazil, to ensure the maintenance and energy security of the National Interconnected System (SIN). In the 2020s, these contracts will end and many thermal plants will face the decommissioning or readjustment of the business plan. This dissertation analyzed the economic viability under risk conditions of a fuel oil thermoelectric plant at the end of an energy supply contract in Brazil. More specifically (i) carried out a Systematic Literature Review (RSL) regarding the perspectives of thermoelectric plants in the energy transition, from the perspective of the circular economy; (ii) analyzed the cost of capital under risk conditions for thermoelectric plants in Brazil; (iii) Analyzed the demobilization under risk conditions for a fuel oil thermoelectric plant in Brazil, and; (iv) analyzed the economic feasibility under risk conditions of a fuel oil thermoelectric plant in Brazil, aiming at replacing the heating system of the fuel storage tanks. For RSL, bibliometrics and content analysis were used. For the economic analyses, the financial statements of the case study were raised and the economic evaluation indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Annual Cost were applied via Monte Carlo Simulation (SMC). Equivalent Uniform (CAUE), Capital Asset Pricing Model (CAPM), Weighted Average Cost of Capital (WACC), Levelized cost of electricity (LCOE) and break even point. The main results showed the importance of thermoelectric plants for energy security, revealing the projects for modernization, implementation, decommissioning, hybrid systems, as well as aspects of the circular economy that aim to increase the efficiency of plants and at the same time reduce environmental impacts; The estimated cost of capital for the thermoelectric plants was a WACC of 11.13% p.a., observed in the local scenario, and 10.32% p.a., in the international scenario. The odds of the local WACC are at most 11.13% p.a. was 68.30% and the global WACC was at most 10.32% p.a. was 48.21%. As a result of the Brazil risk, the cost of local capital was higher when compared to the international scenario; the thermoelectric decommissioning scenarios showed a 100% success, in which the NPV ranged from R$103.73 to 109.73 million and the IRR between 13.55% p.a. and 13.68% p.a., higher than the WACC. With the chances of the NPV being greater than zero, the unfeasibility of the enterprise was ruled out; in the economic study of boiler modernization and replacement, the calculated break-even revenue ranged between R$55.00 and R$66.70 million for the use of Fresnel technology and between R$55.10 and R$70.60 for the use of the boiler. The NPV showed the acceptance of both systems. From the perspective of CAUE and LCOE, Fresnel technology was economically superior, despite the high initial cost. In view of the result of the NPVs, it was more satisfactory to acquire the Fresnel system. It is concluded that it was possible to establish a more realistic discussion in economic analyses, helping to guide public policies, investors, contributing to energy security and the future of fuel oil thermoelectric plants if the continuity of the operation is made possible.